(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Some of the top problems of our country are health issues and lack of medical assistance and services, which cause poverty, especially in areas from hospitals. People suffer from extremely hectic transportation that affects a patient, especially when they came from a rural community. In this study, researchers decided to construct a miniature of a minibus hospital to determine the level of acceptability. Quantitative research was used as the research design for the study. Purposive sampling was used to gather the information of respondents. Using a questionnaire, the researchers conducted a survey to determine whether the proposed project is acceptable in terms of concept, usability, construction materials, and presentation. The results of the study in terms of concept, usability, construction materials, and presentation are highly acceptable, as assessed by mechanical engineers and intern doctors. Results indicated no significant difference between the assessments of the two groups of respondents in terms of the cited variables. This result showed a significant difference between assessments. The difference between the two groups of respondents was not significant. Meanwhile, mechanical engineers obtained an overall weighted mean of 4.65, which was interpreted as very highly acceptable, with a variance of 0.32, a t-computed value of 1.029, and a degree of freedom of 13 with a value of 3.012. The t-computed value was larger than the t-critical one. Therefore, the assessment of mechanical engineers is accepted. Meanwhile, intern doctors obtained an overall weighted mean of 4.29, which was interpreted as highly acceptable with a variance of 0.41, a t-computed value of 1.029, and a degree of freedom of 13 with a value of 3.012. The t-computed value was larger than the t-critical one. Therefore, the assessment of intern doctors is accepted. The subsequent discussions forwarded by the two groups of respondents are as follows. In terms of the concept, several respondents suggested having considerable improvements and study. In terms of usability, several respondents recommended having a CT scan. With regard to construction materials, several respondents suggested to have a wide space for the emergency room. With regard to presentation, several respondents recommended being consistent on some measurements to improve the appearance of the miniature.